2011
DOI: 10.1029/2011gl049764
|View full text |Cite
|
Sign up to set email alerts
|

Solar irradiance, cosmic rays and cloudiness over daily timescales

Abstract: .[1] Although over centennial and greater timescales solar variability may be one of the most influential climate forcing agents, the extent to which solar activity influences climate over shorter time periods is poorly understood. If a link exists between solar activity and climate, it is likely via a mechanism connected to one (or a combination) of the following parameters: total solar irradiance (TSI), ultraviolet (UV) spectral irradiance, or the galactic cosmic ray (GCR) flux. We present an analysis based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 40 publications
(46 reference statements)
0
17
0
Order By: Relevance
“…Throughout this work we will frequently use the cloud data as an anomaly equivalent to A i described in Section 1, with units of %. We again note that the analysis presented here is not meant as a serious test for the hypothesized CRcloud link, for which other similar studies exist (e.g., Laken & Č alogović 2011), but rather is presented for demonstration purposes.…”
Section: Working From the Example Of The Hypothesized Cosmic Ray -Clomentioning
confidence: 99%
See 2 more Smart Citations
“…Throughout this work we will frequently use the cloud data as an anomaly equivalent to A i described in Section 1, with units of %. We again note that the analysis presented here is not meant as a serious test for the hypothesized CRcloud link, for which other similar studies exist (e.g., Laken & Č alogović 2011), but rather is presented for demonstration purposes.…”
Section: Working From the Example Of The Hypothesized Cosmic Ray -Clomentioning
confidence: 99%
“…However, despite extensive research in this area, clear conclusions regarding the validity of a solar-climate link from composite studies have yet to be drawn. Instead, the numerous composite analyses have produced widely conflicting results: some studies have shown positive statistical associations between the CR flux and cloud properties (e.g., Tinsley & Deen 1991;Pudovkin & Veretenenko 1995;Todd & Kniveton 2001, 2004Kniveton 2004;Harrison & Stephenson 2006;Svensmark et al 2009Svensmark et al , 2012Dragić et al 2011Dragić et al , 2013Harrison et al 2011;Okike & Collier 2011), while others find no clearly significant relationships (e.g., Lam & Rodger 2002;Kristjánsson et al 2008;Sloan & Wolfendale 2008;Laken et al 2009;Laken & Č alogović 2011;Laken et al 2012a;Č alogović et al 2010), or even identify significant correlations of a negative sign (e.g., Wang et al 2006;Troshichev et al 2008). We suggest that these ambiguities may result from seemingly minor methodological differences between the composites (e.g., relating to the filtering or normalization of data), which are capable of producing widely divergent results.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, cloud measurements were taken from the International Satellite Cloud Climatology Project (ISCCP) (Rossow and Schiffer 1999). Data from this project have been widely utilized for studying the possibility of a relationship between solar activity and cloud cover (e.g., Pallé and Butler 2000;Todd and Kniveton 2001;Kristjánsson et al 2002;Laut 2003;Marsh and Svensmark 2003;Kristjánsson et al 2004;Č alogović et al 2010;Laken et al 2010Laken et al , 2011. Data from this project have been widely utilized for studying the possibility of a relationship between solar activity and cloud cover (e.g., Pallé and Butler 2000;Todd and Kniveton 2001;Kristjánsson et al 2002;Laut 2003;Marsh and Svensmark 2003;Kristjánsson et al 2004;Č alogović et al 2010;Laken et al 2010Laken et al , 2011.…”
Section: Introductionmentioning
confidence: 99%
“…Others find no change in global cloud cover during FD (Č alogović et al 2010;Laken & Č alogović 2011).…”
Section: Introductionmentioning
confidence: 99%